TRANSFORMASI SOCIAL CROWDFUNDING DI INDONESIA: ANALISIS REGULASI, INOVASI DIGITAL, PERILAKU DONATUR, DAN DAMPAK SOSIAL DALAM PERSPEKTIF LITERATUR - Eka Martyna Theodora; Yenni Yenni; Edi Faisal Harahap (Jurnal Mahkota Bisnis (Makbis), 2025)
The advancement of digital technology has transformed philanthropic practices in Indonesia through the emergence of social crowdfunding. This study aims to integrate empirical findings related to regulatory frameworks, digital innovation, donor behavior, social capital, and social impact of crowdfunding in Indonesia. A systematic literature review was conducted on 20 national scholarly articles published between 2015–2024. The analysis employed thematic classification and conceptual synthesis. The findings indicate that the success of social crowdfunding is influenced by trust, transparency, technological innovation, social capital, and digital communication strategies. Islamic crowdfunding also demonstrates significant potential in strengthening social legitimacy. Regulatory and governance issues remain major challenges. This study proposes an integrative conceptual model explaining the relationship between digital innovation, trust, regulation, donor participation, and social impact in contributing to societal welfare. The findings offer theoretical contributions to digital philanthropy literature and practical implications for regulators and platform managers.